Communication with children and adolescents about the diagnosis of their own life-threatening condition. Issue 10176 (16th March 2019) - ; Betancourt, Theresa; D'Souza, Catherine; Fazel, Mina; Hochhauser, Daniel; Kolucki, Barbara; Lowney, Aoife C; Netsi, Elena; Richter, Linda; Yousafzai, Aisha; Stein, Alan; Dalton, Louise; et al.
Summary: When a child is diagnosed with a life-threatening condition, one of the most challenging tasks facing health-care professionals is how to communicate this to the child, and to their parents or caregivers. Evidence-based guidelines are urgently needed for all health-care settings, from tertiary referral centres in high-income countries to resource limited environments in low-income and middle-income countries, where rates of child mortality are high. We place this Review in the context of children's developing understanding of illness and death. We review the effect of communication on children's emotional, behavioural, and social functioning, as well as treatment adherence, disease progression, and wider family relationships. We consider the factors that influence the process of communication and the preferences of children, families, and health-care professionals about how to convey the diagnosis. Critically, the barriers and challenges to effective communication are explored. Finally, we outline principles for communicating with children, parents, and caregivers, generated from a workshop of international experts.